2012
DOI: 10.1152/ajpgi.00104.2012
|View full text |Cite
|
Sign up to set email alerts
|

The novel growth factor, progranulin, stimulates mouse cholangiocyte proliferation via sirtuin-1-mediated inactivation of FOXO1

Abstract: Progranulin (PGRN), a secreted growth factor, regulates the proliferation of various epithelial cells. Its mechanism of action is largely unknown. Sirtuin 1 (Sirt1) is a protein deacetylase that is known to regulate the transcriptional activity of the forkhead receptor FOXO1, thereby modulating the balance between proapoptotic and cell cycle-arresting genes. We have shown that PGRN is overexpressed in cholangiocarcinoma and stimulates proliferation. However, its effects on hyperplastic cholangiocyte proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…As cholestatic disease progresses, cholangiocytes lose their proliferative capacity in advanced disease, contributing to bile duct loss (ductopenia) . Our results point to the contribution of SIRT1 to this process and support the previously described ability of mild SIRT1 overexpression to inhibit the proliferative effect of growth factors like progranulin in vitro …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As cholestatic disease progresses, cholangiocytes lose their proliferative capacity in advanced disease, contributing to bile duct loss (ductopenia) . Our results point to the contribution of SIRT1 to this process and support the previously described ability of mild SIRT1 overexpression to inhibit the proliferative effect of growth factors like progranulin in vitro …”
Section: Discussionsupporting
confidence: 90%
“…(3) Our results point to the contribution of SIRT1 to this process and support the previously described ability of mild SIRT1 overexpression to inhibit the proliferative effect of growth factors like progranulin in vitro. (38) Ultimately, the apparent differences in severity of the damaging phenotype observed in SIRT1overexpressing mice when compared to SIRT1 hep-/mice, despite the similarly attenuation of FXR signaling, support that apoptotic cell death associated with increased SIRT1 expression play a key role in contributing to liver injury during cholestasis.…”
Section: Discussionmentioning
confidence: 90%
“…SIRT1 is a NAd+ dependent deacetylation enzyme. Frampton G et al have demonstrated that treatment with progranulin, a secreted growth factor, decreased Sirt1 expression and increased the acetylation of FOXO1, resulting in the cytoplasmic accumulation of FOXO1 and enhanced proliferation in cholangiocytes [35]. However the effect of resveratrol on cholangiocarcinoma is far from clear.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the ability of Sirt1 in modulating BA metabolism, very few studies have investigated the Sirt1 pathway in cholestasis. Bile‐duct–ligated models of cholestasis demonstrate decreased hepatic Sirt1 protein expression . However, no further studies have been performed to determine how this down‐regulation affects cholestatic liver injury and whether activation of Sirt1 can alleviate cholestatic liver injury.…”
mentioning
confidence: 99%
“…Bile-duct-ligated models of cholestasis demonstrate decreased hepatic Sirt1 protein expression. (22,23) However, no further studies have been performed to determine how this down-regulation affects cholestatic liver injury and whether activation of Sirt1 can alleviate cholestatic liver injury. The current study aims to: (1) confirm the decrease in expression and activity of Sirt1 in mouse models of cholestasis, (2) determine whether activation of Sirt1 through oral administration of SRT1720 alleviates cholestatic liver injury, and, if so, (3) by what mechanism.…”
mentioning
confidence: 99%